2019
DOI: 10.1111/mmi.14390
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gen locus involved in β‐1,6‐oligosaccharide utilization by Enterococcus faecalis

Abstract: Summary The bicistronic genBA operon (formerly named celBA) of the opportunistic pathogen Enterococcus faecalis, encodes a 6‐phospho‐β‐glucosidase (GenA) and a phosphotransferase system permease EIIC (GenB). It resembles the cel operon of Streptococcus pyogenes, which is implicated in the metabolism of cellobiose. However, genBA mutants grew normally on cellobiose, but not (genA) or only slowly (genB) on gentiobiose and amygdalin. The two glucosides were also found to be the main inducers of the operon, confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In the case of the Enterococcus genus belonging to the Bacilli class, we observed a lower presence in NegativeC but higher prevalence in the MangoB treatment. Although species such as Enterococcus faecalis have been reported as responsible of health problems in the human gut [54], other species such as Enterococcus faecium have been reported as beneficial probiotic microorganisms with the capacity of starting fermented cultures, high acidity and bile salt tolerance that could contribute to reducing serum cholesterol levels [55]. Recently, Wei et al [56] reported that some species of the Enterococcus and Eubacterium genera, have been the guiding forces in the biotransformation of C-C glycosidic bonds, which are present in flavone, xanthone and phenolic acid biomolecules.…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 99%
“…In the case of the Enterococcus genus belonging to the Bacilli class, we observed a lower presence in NegativeC but higher prevalence in the MangoB treatment. Although species such as Enterococcus faecalis have been reported as responsible of health problems in the human gut [54], other species such as Enterococcus faecium have been reported as beneficial probiotic microorganisms with the capacity of starting fermented cultures, high acidity and bile salt tolerance that could contribute to reducing serum cholesterol levels [55]. Recently, Wei et al [56] reported that some species of the Enterococcus and Eubacterium genera, have been the guiding forces in the biotransformation of C-C glycosidic bonds, which are present in flavone, xanthone and phenolic acid biomolecules.…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 99%
“…We found strong evidence for cre sites upstream of the 6S RNA promoter in about a third of all LAB species, mainly in Enterococcaceae but also in Streptococcaceae and some Lactobacillus subgroups. For Streptococcaceae and Enterococcaceae , the presence and regulatory importance of these cre sites has been reported and studied previously [ 59 , 60 ]. On the basis of previous reports, our findings suggest that 6S RNA expression is under the negative control of CcpA in many LAB species.…”
Section: Discussionmentioning
confidence: 99%
“…Three of them code for proteins playing a role in cell metabolism, including the duplication of the gene coding for of the subunit IIB of the lactose/cellobiose PTS system. Different components of the PTS system have also been reported as relevant for E. faecalis colonization (Paulsen et al, 2003), and they have deserved special attention in the last years (Ruiz-Cruz et al, 2015;Sauvageot et al, 2017;Grand et al, 2019).…”
Section: Discussionmentioning
confidence: 99%